Feasibility of copper slag as partial fine aggregate substitute in grout mix applied in rock bolts - Palacol, Christjohn Rhoie C.; Pitogo, Rene Aldous Q.; Timpoc, Froiland S.
Copper slag is an inorganic matter which is a by-product of smelling copper concentrates. Instead of discarding copper slag, it is used as abrasives for sand blasting in shipyards, additives for landfills and aggregates for construction. Other use for copper slag was being studied to discover its other potential as salvaged material. The objective of the research is to determine the feasibility of copper slag as a fine aggregate substitute in grout mix used in rock bolting. The effect of varying concentrations of copper slag and curing time of the grout mix on the peak load capacities of each groups were observed. The host rock were simulated using standard concrete cylinder prepared in accordance to ASTM C31 (Standard Practice for Making and Curing Concrete Test Specimens in the Field) with some modification - a hole was left at the center of the host rock for rock bolting and grouting simulation. The rock bolting was simulated by manual pumping and down-the-hole motion of the corrugated bar was in place. The grout used was composed of different amounts of copper slag replacing the fine aggregates. The different set-up was allowed to cure for different time/duration before subjected to pull-out strength testing. The group that exhibited the highest peak load capacity on one day of curing was the 30% replacement by copper slag of fine aggregate and; for both the seven and fourteen days of curing , the 0% replacement by copper slag of fine aggregate had the most. The findings of the study showed that there was a significant positive correlation between the curing time and the peak load capacity and that out of the copper slag-blended mix, the 30% replacement incurred the highest peak load capacities for all the curing times. The experiment determined the feasibility of copper slag as fine aggregate replacement in grout mix used in rock bolting operations in mines.